Improving pediatric pain management: a comparative analysis of pharmacologic vs. non-pharmacologic treatments - Sahu, Prerana; Patel, Ritesh (Journal of Neonatal Surgery, 2025)
To manage pediatric pain, this study compares the effectiveness of pharmaceutical and non-pharmacologic treatments. A comprehensive review of the literature was carried out, looking at research that evaluates the results of both kinds of child interventions. Although they are frequently used, pharmacologic treatments, such as analgesics and anesthetics, can have long-term effects and adverse effects. Physical therapy, cognitive-behavioral therapy, and alternative therapies are examples of non-pharmacologic treatments that may be beneficial without the risks associated with pharmaceutical interventions. According to the findings, a multimodal strategy that combines pharmaceutical and non-pharmacologic techniques offers the best possible pain relief with the fewest possible adverse effects.